Examining Chinese State-owned Enterprises’ Immunities under the Customary International Law of Sovereign Immunity as Expressed in the United Nations Convention on Jurisdictional Immunities of States and Their Property, the United States Foreign Sovereign Immunities Act, and the United Kingdom State Immunity Act - Hui, Kun (Université d'Ottawa / University of Ottawa, 2023)
The People’s Republic of China (“China”) claims absolute immunity for itself but embraces a concept of state for immunity purposes that excludes state-owned enterprises (“SOEs”). This position has led to confusion and frustration in international litigation against China and Chinese SOEs, particularly when massive Chinese foreign investments are led by SOEs, including those made under China’s Belt and Road Initiative. Yet, the immunity status of Chinese SOEs is unclear. Against this backdrop, this thesis examines Chinese SOEs’ ability to claim sovereign immunity under the customary international law of restrictive immunity as expressed and built on in the 2004 United Nations Convention on Jurisdictional Immunities of States and Their Property (“UNCSI”), the 1976 United States Foreign Sovereign Immunities Act (“US FSIA”) and the 1978 United Kingdom State Immunity Act (“UK SIA”). In investigating the immunity status of the 97 SOEs in which the Chinese central government has direct and full/majority ownership, this thesis answers two questions: (1) under what circumstances would these 97 Chinese SOEs be treated as part of the state for immunity purposes under the UNCSI, the US FSIA and the UK SIA; and (2) under what circumstances would these 97 Chinese SOEs attract jurisdictional and execution immunities thereunder. A critical part of this analysis involves developing an understanding of Chinese SOEs’ dual identity as defined by the Chinese political economy. Chinese SOEs’ dual identity has two levels of meaning. First, it reflects the fact that some Chinese SOEs are categorized as commercial SOEs and others are categorized as public welfare SOEs in the current SOE reform. Secondly, commercial Chinese SOEs have a dual identity, i.e., a commercial and a sovereign aspect in their operations. While commercial SOEs’ primary goal is to pursue commercial interests, they also implement the state’s social, political, and economic policy goals. This sovereign aspect—primarily reflected as the sovereign purpose in their commercial transactions—adds complexity, but is necessary, to our assessment of Chinese SOEs’ “state” status and immunity under the customary international law of sovereign immunity. The three regimes studied in this thesis—the UNCSI, the US FSIA, and the UK SIA—not only take distinctive approaches toward the definition of the state, but also to the commercial exceptions to jurisdictional immunity and execution immunity. Their different analytical frameworks take us to different conclusions about Chinese SOEs’ “state” status and immunity in some cases. Under the UNCSI and the UK SIA, in principle, Chinese SOEs are unlikely to acquire “state” status to claim immunity in their commercial capacity, and consequently, unable to attract jurisdictional immunity and execution immunity for their assets as separate entities. But public welfare SOEs and some commercial SOEs can potentially attract jurisdictional immunity and execution immunity for their assets because to the extent that the purposes of their conduct—which are often related to inherently sovereign functions like the military or the public welfare—are considered in the overall context, the nature of the commercial transaction could be converted into a sovereign one. Under the US FSIA, Chinese SOEs—either commercial or public welfare ones—are state agencies/instrumentalities for immunity purposes, thus, have “state” status. But, in contrast with the UNCSI and the UK SIA, Chinese SOEs are less likely to attract jurisdictional immunity for their commercial activities or execution immunity for their assets under the US FSIA because the US statute applies a broad commercial exception that only considers the nature of the conduct in characterizing whether a transaction is a commercial one. This thesis’s investigations and conclusions have commercial, sovereign, and policy implications for Chinese SOEs’ international business transactions, China’s sovereign immunity position, and litigation involving China and Chinese SOEs in jurisdictions where restrictive immunity is upheld. First, in commercial terms, the analysis in this thesis will better enable commercial parties and states that have commercial relations with Chinese SOEs to understand the dual identity of Chinese SOEs defined by the Chinese political economy and understand under what circumstances Chinese SOEs can potentially attract jurisdictional and execution immunities. Second, in sovereign terms, my research enables states to assess their diplomatic and economic relationships with China from a foreign relations law perspective as China asserts absolute immunity in foreign domestic courts. As this thesis suggests, litigation against China and its emanations and execution against their assets in states where restrictive immunity is applied could give rise to sensitive political clashes in light of China’s absolute immunity position. The ongoing pandemic litigation between the State of Missouri and China in the US court is an example. In line with its practice, China refused to appear in this and other similar cases. My thesis work could provide legal researchers and practitioners with a better informed legal perspective on these highly political disputes. Third, in policy terms, my Chapter on China’s sovereign immunity and my findings that some commercial and public welfare SOEs can potentially attract jurisdictional and execution immunities under the UNCSI and the UK SIA provide China some reasons to not only embrace restrictive immunity but to clarify the definition of the state for immunity purposes thereunder. Ratifying the UNCSI, in my view, would allow China’s position to conform to international law on the one hand; and allow China to contribute to the development of the law of sovereign immunity on the other hand.
Keywords: state immunity; sovereign immunity; China; state-owned enterprises; SOEs